2018
DOI: 10.1515/cclm-2018-0139
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of mucin 13 (MUC13) as a biomarker for carcinomas and other diseases

Abstract: Serum MUC13 is frequently elevated not only in a variety of malignant cases but also in some benign pathologies, thus appearing to be a non-specific disease biomarker. Nonetheless, serum MUC13 is clearly highly elevated in some carcinoma patients, and its relationship with tumor progression in this context warrant further research. Future studies that examine the correlation between serum MUC13 levels to stage of cancer could elucidate prognostic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…For example, microbiota can feed on mucin glycans and convert them into SCFAs that supply colonocytes and other gut epithelial cells with energy ( Ouwerkerk et al, 2013 ). Interestingly, MUC13 is abundant in many adenocarcinomas ( Sheng et al, 2019 ), where it serves as a potential prognostic factor ( Filippou et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, microbiota can feed on mucin glycans and convert them into SCFAs that supply colonocytes and other gut epithelial cells with energy ( Ouwerkerk et al, 2013 ). Interestingly, MUC13 is abundant in many adenocarcinomas ( Sheng et al, 2019 ), where it serves as a potential prognostic factor ( Filippou et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genes highly expressed in epithelial or lung cells and significantly induced after nano-carbon black treatment, included MUC2 , MUC3A , MUC13 , MUC17 , GSTA1 , GSTA2 , FABP2 , APOA1 , APOA2 , APOA4 , and APOB (Excel Table S2E,H). Among these, MUC and GSTA genes have been largely correlated to or identified in lung and other cancers. Meanwhile, FABP2 and APO genes, encoding for different apolipoproteins, might indicate changes in metabolism considered to play protective roles in lung diseases. Thus, nano-carbon black treatment might promote the expression of cancer-related genes and trigger signaling pathways to facilitate the metabolism of xenobiotic nanoparticles and defensive systems. Indeed, KEGG enrichment analyses demonstrated that chemical carcinogenesis and metabolic pathways were significantly promoted after nano-carbon black treatment (Figure E, and Excel Table S2F,G).…”
Section: Resultsmentioning
confidence: 99%
“…(3) Mucin-13 is a cell surface glycoprotein that is abnormally expressed in various epithelial cancers. Serum mucin 13 is elevated in 70% of active skin melanoma patients (except for uveal melanoma) [27]. (4) Alpha-cardiac actin is involved in various types of cell movements.…”
Section: B16 Melanoma-bearing Micementioning
confidence: 99%